Epidemiologia da linfadenite caseosa ovina no estado de Minas Gerais, Brasil - Alessandro de Sa Guimaraes (2009)
Caseous Lymphadenitis (CL) is a diesease of worldwide occurrence caused by Corynebacterium pseudotuberculosis. It inflicts considerable economic losses due to decreased wool, meat, and milk production, impaired reproduction efficiency, and carcass and leather condemnation due to abscesses. A review of the literature concerning CL was made and incorporated into this thesis. The lack of information about the serological status of sheep herds in Minas Gerais, Brazil, motivated the serological survey herein described. Ovine sera (n=642) collected from 97 properties in the State of Minas Gerais, Brazil, in 2002 were analyzed by Indirect ELISA tests. Additionally, questionnaires were filled out for the producers surveyed. The real prevalence of positive animals was 75.8%, with 95.9% of herds positive for CL. There was no relation between positive serology and gender, although age over 12 months and pureBrazilian breeds (Santa Inês, Morada Nova, and Somalis breeds) were related to positive serology. No producer stated to use vaccine against CL. Despite the high positive serology of both animals and herds, only 11.3% of producers stated to have CL in their properties. Most producers (93.8%) affirmed not to segregate animals with clinical signs of CL from the herd, 77.3% don't identify animals individually, and 58.8% reported to have technical assistance available. In 2007, suppliers of sheep to a slaughterhouse in Patrocínio, Minas Gerais, Brazil, were characterized by a questionnaire. Defficient management for control of CL was detected inthe answers, since no producer stated to eliminate animals with clinical CL, only 3.3% burned and buried the material from manipulation of abscesses, 98.3% didn't use any drainage after abscess manipulation, and 86.7% of producers kept no record of animals with clinical signs ofCL. Moreover, abscesses were visualized most frequently around the head and neck, only 1.7% of producers culled animals with recidiving abscesses, 10% knew the zoonotic potential of CL, and 11.7% of concerns had veterinary assitance available. Still in 2007, a seroepidemiological characterization of CL in this same region was performed. Ovine sera (n=805) from 23 supplier properties and caseous material (n=285) from 21 supplier properties were sampled. Allconcerns were positive for CL, while 46.8% of slaughtered animals were positive. Superficial lymph nodes were diseased in 15.3% (348/2,270) of carcasses, 8.9% (203/2,270) of viscera (lungs, liver, and intestines) had at least one abscess, and 0.6% (14/2,270) of carcasses were condemned. C. pseudotuberculosis was isolated and identified by morphologic and staining characteristics, biochemical analysis, and multiplex PCR in 72.6% (207/285) of pus samples collected.